Children, Childhood and Youth in the British World
XIII, 328 p.
Keywords: Age was a critical factor in shaping imperial experience, yet it has not received any sustained scholarly attention. This pioneering interdisciplinary collection is the first to investigate the lives of children and young people and the construction of modes of childhood and youth within the British world.